A Bioassay Technique to Study Clomazone Residues in Sandy Loam Soil (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
A bioassay test was conducted to evaluate the sensitivity of maize, sunflower and barley to clomazone residues in sandy loam soil. Clomazone was applied at different rates from 0.12 to 12 mg a.i./kg of soil. The parameters measured 14 days after treatment were: shoot height, fresh and dry weight, and content of pigments (carotenoids, chlorophyll a and chlorophyll b). The results showed that the lowest clomazone concentration caused a significant reduction in all measured parameters for barley and sunflower shoots. Fresh weight of maize shoots was not sensitive to clomazone residual activity in soil while the other parameters were highly inhibited. Nomenclature: clomazone (2-(2-chlorbenzyl)-4,4-dimethyl-1,2-oxazolidin-3-one), maize (Zea mays L.), sunflower (Helianthus annuus L.), barley (Hordeum vulgare L.)
Keywords: Sunflower; Bioassay; Residues; Maize; Clomazone; Barley